2022
DOI: 10.1017/s0033291722002550
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic experiences in the general population, a review; definition, risk factors, outcomes and interventions

Abstract: Psychotic experiences (PE) are common in the general population, in particular in childhood, adolescence and young adulthood. PE have been shown to be associated with an increased risk for later psychotic disorders, mental disorders, and poorer functioning. Recent findings have highlighted the relevance of PE to many fields of healthcare, including treatment response in clinical services for anxiety & depression treatment, healthcare costs and service use. Despite PE relevance to many areas of mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 172 publications
(263 reference statements)
0
41
0
Order By: Relevance
“…CUES is designed to reduce emotional/ behavioural problems, particularly for vulnerable children, by promoting emotional literacy and emotional/ behavioural regulation, both linked with childhood social and academic functioning [14,15]. CUES also aims to reduce cognitive vulnerability to mental health problems by reducing stigma and promoting flexible thinking and normalising explanations of unusual perceptual experiences, such as seeing or hearing things which others cannot [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CUES is designed to reduce emotional/ behavioural problems, particularly for vulnerable children, by promoting emotional literacy and emotional/ behavioural regulation, both linked with childhood social and academic functioning [14,15]. CUES also aims to reduce cognitive vulnerability to mental health problems by reducing stigma and promoting flexible thinking and normalising explanations of unusual perceptual experiences, such as seeing or hearing things which others cannot [16].…”
Section: Discussionmentioning
confidence: 99%
“…Scores range from 0 to 20, with lower scores indicating more positive outcomes (clinical cut-off > 9). • M&MF-B 6-item subscale (M&MF items [11][12][13][14][15][16] at 16 weeks. Scores range from 0 to 12, with lower scores indicating more positive outcomes (clinical cut-off > 5).…”
Section: Vulnerable Sub-populationmentioning
confidence: 99%
“…Psychotic disorders are rare conditions characterized by a constellation of symptoms including hallucinations, delusions, negative symptoms, and thought disorder. However, recent decades of research have shown that psychosis can occur in the general population without reaching a clinical level of impairment or distress (Linscott & Van Os, 2010; Staines et al, 2022). In the United States, for example, approximately 10–20% of the general adult population report a psychotic experience at some point in life depending on how psychotic experiences are measured (Cohen & Marino, 2013; Oh et al, 2020), and most of these individuals will not develop a psychotic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…10 This means that positive psychotic symptoms in adolescents and young adults are predictive for a wide range of negative outcomes, including the development of psychotic and nonpsychotic mental disorders, multimorbidity, functional impairments, and suicidal behavior. 11 Thus, they are no longer seen as pathognomic for psychotic disorders such as schizophrenia, but may be understood as a transdiagnostic risk maker for severe psychopathology and impairment. In addition, there is increasing evidence suggesting that affective instability and emotional reactivity to stress are related to psychotic experiences along the continuum.…”
mentioning
confidence: 99%
“…Even though they are most prevalent in childhood (with decreasing prevalence rates over the rest of the life span), they become more clinically significant with the transition into adolescence and early adulthood 10 . This means that positive psychotic symptoms in adolescents and young adults are predictive for a wide range of negative outcomes, including the development of psychotic and non‐psychotic mental disorders, multimorbidity, functional impairments, and suicidal behavior 11 . Thus, they are no longer seen as pathognomic for psychotic disorders such as schizophrenia, but may be understood as a transdiagnostic risk maker for severe psychopathology and impairment.…”
mentioning
confidence: 99%